Evaluation of some physical and chemical properties of hazelnuts - Guiné, Raquel (2019)
In this work were evaluated some physical and chemical properties of hazelnuts from two varieties (Buttler and Longa), namely colour, texture and density at the physical level and moisture, total fat, fat oxidation, ash, protein and crude fibre as concerns the chemical composition, following established procedures. The results obtained showed that the colour of the hazelnuts varied according to the point of measurement and also depending on the variety, being the Longa clearer in all points except for the core, in which the colour was equal to Butler. Regarding texture, the Butler was harder in the shell but softer in the core as compared to Longa, which in turn showed higher friability. Regarding density, no visible differences were found between varieties, but the bulk density was naturally lower than the true density in all cases, i.e., for measurements made with and without the shell, respectively. The moisture content was higher for Butler variety, 7.13%, and this also had the highest water activity. The fat content was high, as expected, around 60% in both cases, and the time for fat oxidation was lower for the Butler variety, thus indicating a lower stability to oxidative degradation. The ash content was higher for Longa variety, which was also richer in terms of protein, 15.60 %. The fibre content, however, was higher for Butler variety, 11.11%.